On Black Holes - Falciano, Felipe Tovar (Cadernos de Astronomia, 2023)
Black holes are astrophysical objects with very particular and fascinating properties. Starting from generic hypotheses, such as the validity of the theory of general relativity, it is possible to prove theorems that guarantee the existence and properties of these objects. However, only observation and experiments are capable of testing and verifying statements about natural phenomena. Following this reasoning, we will develop the basic concepts of what a black hole is, explain some of its peculiar properties, and finally punctuate the observations that prove the existence of these compact objects.